أثر تصنيف الاستدامة البيئية والاجتماعية والحوكمة في السعر السوقي للسهم : دراسة تطبيقية على البنوك الاسلامية العاملة في دول مجلس التعاون الخليجي: The Impact of Environmental, Social and Governance (ESG) Sustainability Rating on the Market Price of Shares: An Applied Study on Islamic Banks Operating in the GCC Countries - Ahmad Abu Mousa, Huda; Ahmad Abu Mousa, Rasmiah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث هدفت هذه الدراسة إلى بيان أثر تصنيف الاستدامة البيئية والاجتماعية والحوكمة (ESG) من قبل شركة Sustainayltics في السعر السوقي لسهم البنوك الإسلامية العاملة في دول مجلس التعاون الخليجي خلال الفترة من 2022-2024. واشتملت عينة الدارسة على (12) بنكا إسلاميا حاصلا على تصنيف من قبل الشركة ،واتبعت الدراسة منهجا وصفيا تحليلا باستخدام معادلة الانحدار الخطية البسيطة . وقد توصلت الدراسة إلى وجود أثر إيجابي وبعلاقة متوسطة لتصنيف الاستدامة والسعر السوقي، وأنه لا يوجد أثر ذا دلالة إحصائية لتصنيف الاستدامة والسعر السوقي لأسهم البنوك قيد الدراسة. وأوصت الدارسة بضرورة إفصاح البنوك الإسلامية عن تقارير الاستدامة، وعمل دراسات لفترة زمنية أطول وعينة تشمل بنوكا إسلامية أشمل، وإدخال متغيرات تؤثر على السعر السوقي لإثراء الدراسة. ABSTRACT This study was aimed at demonstrating the impact of the ESG classification on the market price of Islamic banks operating in the GCC from 2022-2024. The study sample included 12 Islamic banks with a rating was conducted by Sustainayltics .The study followed a descriptive analytical approach using a simple linear regression equation. The study found a positive impact and an intermediate relationship to the classification of sustainability and market price, there is no statistically significant impact of the sustainability classification and market price of the banks’ shares under consideration. The study recommended that Islamic banks should have disclosed sustainability reports and longer-term studies with more comprehensive and variables sample affecting the market price in order to enrich the study.